Emancipar-se é conhecer-se, emancipar-se é realizar-se : a emancipação feminina na Revista da Semana (1927-1934) - Pastelletto, Nielly da Silva (2021)
In the first half of the 20th century, Brazil is going through an intense period of modernization. This modernization can be seen in the technologies that provided a frank expansion of the Brazilian press, especially in the Federal District, as well as it was a period of social transformation, which included the progressive occupation of women in public environments and consequently altered their role in society. In the meantime, Revista da Semana was created, a periodical from Rio de Janeiro founded in 1900, which remained active until 1959, and established itself as a pioneer in the massive use of photographs. The objective of this work is to investigate how the magazine approached issues related to female emancipation at this moment of national effervescence, specifically between the years 1927 and 1934, important markers for the achievement of women's rights. When talking about emancipation, we considered content that concerns issues related to women's work, voting and education. In addition to using the Revista da Semana as a source, it will be analyzed as an object, to achieve this goal, the Content Analysis methodology was used.